Sistem Aplikasi Presensi Menggunakan Fingerprint Sebagai Monitoring Orang Tua Terhadap Kehadiran Mahasiswa Polman Babel Berbasis IoT - Sari, Alfi Aulia; Vatuzulaika, Iche Dinitia; Maulana, Muhammad Melky; Sulistyo, Eko; Afriansyah, Riki (Jurnal Inovasi Teknologi Terapan, 2025)
A student attendance system based on Internet of Things (IoT) technology with fingerprint sensors and whatsapp notifications was developed to improve accuracy, efficiency, and security in recording attendance in an educational environment. This research aims to design and implement an attendance system that utilizes fingerprint sensors to authenticate student attendance data legally and sends realtime notifications to parents via WhatsApp. The development process begins with data collection through literature studies and needs analysis to design the required features. The system is designed by integrating hardware in the form of fingerprint sensors and IoT modules and software that includes mobile applications and framework-based websites. Testing is carried out in stages, from unit tests to integration tests, to ensure all components work properly. System implementation involves the use of tools by students and lecturers as well as regular maintenance to ensure operational sustainability. The results show that this system is able to reduce the potential for fraud in attendance, improve the efficiency of recording, and strengthen communication between the campus and parents. Thus, this system is expected to be an effective solution in overcoming attendance problems in higher education, especially at the Bangka Belitung State Manufacturing Polytechnic.